(3GdeaGgje heYGjjQ GdbjGS hGdEaUGM GdeMGSHjs - (3eMeO SejQ(B, (3GdUHGfs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 1998)
(3jJfGhd gPG GdcJGH HYV ehVhYGJ GdeMGSHI GdeJhSWI hbO Je JbSje gPG GdcJGH Edi KdGK eOGNd HGdEVGaI Edi JeGQjf aj GdeMGSHIs
Keywords: (3GdbjGSs; (3GdeMGSHIs